Bisoprolol Therapy and The Risk of Erectile Dysfunction in Stable Coronary Artery Disease Patients - Firman Fauzan; Bambang Irawan; Hariadi Hariawan (ACI (Acta Cardiologia Indonesiana), 2016)
Background :Bisoprolol is an anti angina and ischemic therapy in patient with stable coronary artery disease (CAD). Moreover it can decrease mortality and rehospitalization rate up to 34 % and 28 %. However it is also known to increase erectile dysfunction risk. Leydig cells has beta receptor which contribute in testosterone release. The blockade of beta receptor by bisoprolol can inhibit testosterone release and cause erectile dysfunction (ED) Method :This retrospective case control study was done by age matched paired method. Men with CAD as diagnosed by angiography were evaluated for ED. Erectile function was assessed by a 5-item version of the International Index of Erectile Function (IIEF-5). History of disease and medical record were evaluated to check history of bisoprolol therapy for the last 6 month. Depression was screened using Indonesian version of Hospital Anxiety and Depression Scale (HADS). Result : From 157 total subject, patients were divided into 105 patients in case group and 52 patients in control group. Ninety patients (85.7%) had history of bisoprolol therapy. The odd ratio of bisoprolol to have ED risk was 2, but there was not significant statistically (95% CI 0.85- 2.93; p= 0.262). From sub analysis result 5 mg bisoprolol therapy have significant statistic result to ED risk (OR 2.65, 95% CI 1.12-6.25; p=0.026). Diabetes was another confounding factor which have significant risk to ED from multivariate analysis result (OR 3.8, 95 % CI 1.65-8.88, p=0.002). Conclussion : Stable CAD patients with bisoprolol therapy have a higher risk of ED compare with stable CAD patient without bisoprolol, however it was not statistically significant.Keywords : Bisoprolol; erectile dysfunction; stable coronary artery disease